A photometric analysis of the neglected EW-type binary V336 TrA - W. Kriwattanawong (2018)
© 2017 Elsevier B.V. This study presents an analysis of photometric light curves and absolute parameters for the EW-type binary V336 TrA. VRI imaging observations were taken in 2013 by using the robotic telescopes PROMPT 4 and PROMPT 5 at Cerro Tololo Inter-American Observatory (CTIO), Chile. The observed light curves were fitted by using the Wilson–Devinney method. The results showed that V336 TrA is a W-type contact binary with a mass ratio of q = 1.396. The binary is a weak contact system with a fill-out factor of f = 15.69%. The system contains components with masses of 0.653 M ⊙ and 0.912 M ⊙ for the hotter and the cooler, respectively. The location of the secondary (less massive) component on the log M−log L diagram was found to be near the TAMS. The component has evolved to be oversize and overluminous. The orbital angular momentum of the binary was found to be log J o = 51.61 cgs, less than all detached systems for same mass. The system has undergone angular momentum and/or mass loss, during the binary evolution from the detached to contact system.